Access to improved water and its relationship with diarrhoea in Kathmandu Valley, Nepal: a cross-sectional study. Issue 6 (28th June 2013) - Shrestha, Salina; Aihara, Yoko; Yoden, Kanako; Yamagata, Zentaro; Nishida, Kei; Kondo, Naoki
Abstract : Objective: To assess the associations between diarrhoea and types of water sources, total quantity of water consumed and the quantity of improved water consumed in rapidly growing, highly populated urban areas in developing countries. Design: Cross-sectional analysis using population-representative secondary data obtained from an interview survey conducted by the Asian Development Bank for the 2009 Kathmandu Valley Water Distribution, Sewerage and Urban Development Project. Setting: Kathmandu Valley, Nepal. Participants: 2282 households. Methods: A structured questionnaire was used to collect information from households on the quantity and sources of water consumed; health, socioeconomic and demographic status of households; drinking water treatment practices and toilet facilities. Results: Family members of 179 households (7.8%) reported having developed diarrhoea during the previous month. For households in which family members consumed less than 100 L of water per capita per day (L/c/d), which is the minimum quantity recommended by WHO, the risk of contracting diarrhoea doubled (1.56-fold to 2.92-fold). In households that used alternative water sources (such as wells, stone spouts and springs) in addition to improved water (provided by a water management authority), the likelihood of contracting diarrhoea was 1.81-fold higher (95% CI 1.00 to 3.29) than in those that used only improved water. However, access to an improved water source was not associated with a lower risk of developing diarrhoea if optimal quantities of water were not consumed (ie, <100 L/c/d). These results were independent of socioeconomic and demographic variables, daily drinking water treatment practices, toilet facilities and residential areas. Conclusions: Providing access to a sufficient quantity of water—regardless of the source—may be more important in preventing diarrhoea than supplying a limited quantity of improved water.